O SOLDADO DE FRONTEIRA: TRADIÇÃO, MEMÓRIA E MASCULINIDADES NO 4ºGACav-II/1ºRADC (1926/ 1943) - Batista , Maria Gisele Vargas (2018)
This dissertation aims to analyze the 4th GACav-II / 1ºRADC, military unit existing in Santo Ângelo, Rio Grande do Sul, between 1926 and 1943. We seek to understand how the representation of heroes, the emphasis on remembrance, the invention of the military tradition, the activities developed in the barracks, sought to form an ideal military masculinity, in this border region. Our main source of research is the "Historical Book of II / 1ºRADC of the 3rd Military Region", which is composed of handwritten notes and bulletins of this military unit, in addition to laws and decrees of the same period. This documentation, written since 1926, was added as a Historical Book in 1943. In theoretical terms we approach conceptions of the New Military History and the New Cultural History, which gave a framework to the discussion about how these border soldiers were forged and how the hegemonic masculinity for this group. This approach allows us to analyze the creation and installation of the mentioned military unit, including defense policies, the choice of frontier region and Horse Artillery, as well as to understand how the construction of memory, the remembrance of traditions and the construction of heroes through the narratives of bulletins contained in the Historical Book of the military unit of Saint Angelo. In addition, we admit the analysis of the narratives of representation of masculinity (s) and construction of the "military man". In this way, it was possible to understand how representations of heroicity, invented traditions, memory, recollection, normalized and hierarchical activities were used to invent a hegemonic masculinity, which was intended, inscribed in the bodies of these soldiers.